Gait ability analyse in senior age 65+ related to the quality of life indicators - Krejčí, Milada; Hill, Martin; Jandová, Dobroslava; Górny, Mirosław Paweł; Kajzar, Jiří (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. In the study the gait indicators measured by the Tinetti Gait Test are analysed in correlation to indicators of the quality of life of seniors according to the RAND 36 Short Form Health Survey (SF-36). Aim of Study. Main aim of the presented study is to point out the gait ability of seniors aged sixty-five and older in the complexity analysis of bio-psychosocial approach. Material and Methods. The research sample for the study consisted of 500 seniors of the Czech Republic, selected by randomized selection from all Czech regions, from seniors’ houses. The monitored seniors were in age 65 years and older (mean: 75.9 SD ± 7.14), 234 males (mean: 74.5 SD ± 7.74) and 266 females (mean: 76.9 SD ± 7.23). The seniors participated in the investigation voluntarily on the base of signed informed consent. Diagnostic methods: medical anamnesis; functional anthropological examination; Tinetti Gait Test; RAND 36 Short Form Health Survey (SF-36). Statistics: multivariate regression with reduction of dimensionality, method of orthogonal projection to latent structure. Results. The created linear regression model was highly statistically signiﬁcant (p < 0.001) and showed high selectivity as well as high speciﬁcity to the SF-36 items. The clinical validity of the model demonstrated a 72% predictive value for the detection and an 87% successful speciﬁcation of the items of health survey SF-36 in correlation to the Tinetti Gait Test. Also higher age of seniors, number of taken medicaments, health problems as diabetes, sclerosis multiplex, haemorrhage, heart problem and stroke are in significant negative correlation to the Tinetti Gait Test result. Conclusions. The study demonstrated the possibility of the gait ability in seniors 65+ may be searched very closely and significantly related to the physical, psychic and social quality of life indicators. The analysed predictors to the successful gait ability development are inspiration for experts, which focus their work on kinesiotherapy and adapted physical education in senior age.
Keywords: ageing; balance; gait disorders; health support; quality of life